O(s) fascismo(s) no livro didático: uma análise do conteúdo no ensino fundamental e médio - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The objective of this Final Master's Work was to analyze the context of the textbook of the Elementary School called Meetings with the History of the authors of the authors Vanise Ribeiro and Carla Anastasia (2016) and the High School Paths of Man (2016) by the authors Adhemar Marques and Flávio Berutti ( 2016) on fascism (s). Francisco Carlos Teixeira da Silva (2005) brings a new discussion about Nazi-fascism approaching the new possibilities of stratifying fascism from the end of the 1980s, when there is a turnaround in the academic scene from the analysis of new sources. It is important to dialogue with Silva's provocative text (2008) regarding fascism, since it launches a more present critical discussion, given that one of the most well-known and immediate post-war approaches, popularized in the media, fascism, defends a unique approach of the phenomenon, focusing all the attention in Germany and using exclusively the expression Nazism. Such a situation can be found in the context of the textbook that usually builds a narrative focus that centralizes the theme in World War II and the character of Adolf Hitler. Going back to the textbook, this object may or may not attempt to link the past with the present, since it must corroborate the critical construction of young people and their perceptions and positions regarding society. In the case of this research raised by Silva (2005) as a phenomenon, we investigate if there is any relation between the aspects presented in the two Didactic Books of elementary and high school that we selected for analysis. In this sense, we present a chapter in which we discuss the concept (s) of fascism (s) and explore the reality of elaborating a didactic book and how it can approach certain topics such as Nazi-fascism. In the second chapter we analyzed two textbooks used in the city of Ipameri - GO in the year 2017, Meetings with History used in the 9th year of elementary school and Paths of Man used in the 3rd. year of high school. In the annex we present a Reference Guide with the purpose of allowing the teacher, from different sources, to relate the theme to the present.
(S) fascismo (s) en el libro didáctico: un análisis del contenido en la enseñanza fundamental y medio
Keywords: Fascismos; Livro didático; Ensino de história; Fascism; Didactic book; History teaching; CIENCIAS HUMANAS::HISTORIA